Shoulder-sideWINDER (Shoulder-side Wearable INDustrial Ergonomic Robot): Design and Evaluation of Shoulder Wearable Robot With Mechanisms to Compensate for Joint Misalignment - Park, Daegeun; Toxiri, Stefano; Chini, Giorgia; Natali, Christian Di; Caldwell, Darwin G.; Ortiz, Jesus (IEEE transactions on robotics, 2022)
Shoulder-sideWINDER is an exoskeleton to assist the shoulder movement of workers performing manual tasks. It aims to minimize discomfort caused by a joint misalignment between the shoulder and an exoskeleton, which is a common problem with many closely coupled systems. Based on the shoulder's musculoskeletal structure, we propose two novel misalignment correction mechanisms: center-of-rotation tracking mechanism and force-guiding mechanism. The center-of-rotation tracking mechanism compensates for the vertical misalignment that arises from the scapulohumeral rhythm. The force-guiding mechanism compensates for the horizontal misalignment due to changes in the plane of the arm elevation. The kinematic performance of reducing joint misalignment was evaluated using the angle ratio as the indicator under two conditions: with and without the center-of-rotation tracking mechanism. The muscle load caused by the kinematic disturbance was evaluated under three conditions: wearing the exoskeleton with and without the center-of-rotation tracking mechanism and not wearing the exoskeleton. The analysis used muscle load data measured by surface electromyography on five shoulder muscles. Five subjects executed 12 arm motions each, in 4 planes of elevation. Since the system was optimized for a pilot user, subjects with similar morphology presented positive results showing that the proposed mechanism reduced the misalignment in the dominant range of working motion. Apart from the anterior deltoid, the loads on muscles responsible for the dominant range of working motion also showed a significant reduction compared to the case without the mechanism. In conclusion, we verified that the Shoulder-sideWINDER provides comfortable support by reducing joint misalignment, and identified directions for design improvements that will further enhance usability.